Effects of Krankcycle Training on Performance and Body Composition in Wheelchair Users - Čichoň, Rostislav; Maszczyk, Adam; Stastny, Petr; Uhlíř, Petr; Petr, Miroslav; Doubrava, Ondřej; Mostowik, Aleksandra; Gołaś, Artur; Cieszczyk, Paweł; Żmijewski, Piotr (Journal of human kinetics, 2015)
Innovation in training equipment is important for increasing training effectiveness, performance and changes in body composition, especially in wheelchair users with paraplegia. The main objective of a workout session is to induce an adaptation stimulus, which requires overload of involved muscles by voluntary effort, yet this overload may be highly influenced by the size of the spinal cord lesion. Krancykl construction is designed to allow exercise on any wheelchair and with adjustable height or width of crank handles, where even the grip handle may be altered. The aim of this study was to determine the differences in body composition, performance and the rate of perceived exertion (RPE) in paraplegics with a different level of paralyses after a 12 week training programme of a unilateral regime on Krankcycle equipment (a crank machine). The study sample included four men and one women at a different spine lesion level. The 12 weeks programme was successfully completed by four participants, while one subject got injured during the intervention process. Three participants were paraplegics and one was quadriplegic with innervation of the biceps humeri, triceps humeri and deltoideus. The Krankcycle 30 min programme was followed by four other exercises, which were performed after themselves rather than in a circuit training manner as the latter would result in much longer rest periods between exercises, because paraplegics have to be fixed by straps during exercise on hydraulic machines. The RPE after the workout decreased following the twelve week adaptation period.